Bera chosen for the UMPSA TVET Promotional Tour - Naqiah, Puaad (UMPSA, 2024)
BERA, 28 July 2024 – The Bera District was the chosen destination for this edition of the Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) TVET Promotion Tour.